Job Satisfaction and Organisational Commitment of College Library Professionals: A Case Study - Dutta, Saurabh; Singh, Parminder; Wagay, Javaid Ahmad (Journal of Information and Knowledge, 2025)
Purpose: The primary objective of this study is to investigate the job satisfaction levels of library professionals employed in the libraries of colleges affiliated to Punjab University, Chandigarh. Design/Methodology: Descriptive research design is used in this study with a view to providing an accurate representation of the subject being studied without influencing it. Findings: Most colleges have full-fledged working librarians. Female library professionals working in the colleges are more in number and were found to be less satisfied with their jobs than their male counterparts. The majority of employees are content with their jobs and are dedicated to their respective organisations. The relationship between job satisfaction and organisational commitment is average, showing a moderate link between the two variables. The correlation was higher for library professionals working in government colleges, indicating a higher degree of satisfaction. Professionals at the level of Assistant Librarians are the most content and dedicated to their organisations.